2012
DOI: 10.1158/0008-5472.can-11-3069
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Ceramide Transfer Protein Augments EGF Receptor Signaling in Breast Cancer

Abstract: Triple-negative breast cancers (TNBC) are especially refractory to treatment due to their negative hormone receptor and ErbB2/HER2 status. Therefore, the identification of cancer-associated deregulated signaling pathways is necessary to develop improved targeted therapies. Here, we show that expression of the ceramide transfer protein CERT is reduced in TNBCs. CERT transfers ceramide from the endoplasmic reticulum to the Golgi complex for conversion into sphingomyelin (SM). We provide evidence that by regulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 47 publications
0
34
0
1
Order By: Relevance
“…In addition, TNBC are aggressive because of their frequent recurrence and high metastatic potential (37). Ceramide transfer protein (CERT) was recently reported to determine the signaling output of the EGF receptor (EGFR/ErbB1), which is upregulated in TNBC (38). Reduced expression of CERT in TNBC is associated with alterations in plasma membrane organization and PLD2 activation (38).…”
Section: Role Of Pld Up-regulated In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, TNBC are aggressive because of their frequent recurrence and high metastatic potential (37). Ceramide transfer protein (CERT) was recently reported to determine the signaling output of the EGF receptor (EGFR/ErbB1), which is upregulated in TNBC (38). Reduced expression of CERT in TNBC is associated with alterations in plasma membrane organization and PLD2 activation (38).…”
Section: Role Of Pld Up-regulated In Cancermentioning
confidence: 99%
“…Ceramide transfer protein (CERT) was recently reported to determine the signaling output of the EGF receptor (EGFR/ErbB1), which is upregulated in TNBC (38). Reduced expression of CERT in TNBC is associated with alterations in plasma membrane organization and PLD2 activation (38). Heering et al (38) suggested that the loss of CERT might trigger aberrant ligand-induced ErbB1 signaling through PLD2 activation, which may be relevant to the design of therapeutic interventions targeting TNBC.…”
Section: Role Of Pld Up-regulated In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cells are known to evade the immune system by downregulating complement activation (56). Interestingly, a recent study found downregulation of CERT in cancers refractory to treatment (57). Thus, the loss of CERT could be a mechanism by which tumor cells reduce complement activation, resulting in reduced clearance of tumor cells by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, in Immune system, all kinds of immunoglobulins are glycoproteins. It is reported that Cert expression decreases in Triple Negative Breast Cancer (TNBC), an aggressive cancer type in metastasis [7]. Consistent with the recent discovery [8]: Lipid rafts and its associated actin cytoskeleton contribute to the localization and function of ABC transporter, the marker of side population in flow cytometry, our unpublished data with head and neck Squamous cell carcinoma (HNSCC) suggest that hypoxia induces the characteristic of cancer stem cell, hormone and growth factor enhance hypoxic response of HNSCC, which are probably the reason of resistance to chemotherapy for cancers.…”
Section: Editorialmentioning
confidence: 99%